2020
DOI: 10.2147/ijn.s287456
|View full text |Cite
|
Sign up to set email alerts
|

<p>Targeted Delivery of Erythropoietin Hybridized with Magnetic Nanocarriers for the Treatment of Central Nervous System Injury: A Literature Review</p>

Abstract: Although the incidence of central nervous system injuries has continued to rise, no promising treatments have been elucidated. Erythropoietin plays an important role in neuroprotection and neuroregeneration as well as in erythropoiesis. Moreover, the current worldwide use of erythropoietin in the treatment of hematologic diseases allows for its ready application in patients with central nervous system injuries. However, erythropoietin has a very short therapeutic time window (within 6-8 hours) after injury, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 164 publications
(221 reference statements)
0
5
0
Order By: Relevance
“…Similar to delivery studies with other therapeutics, most EPO delivery trials have focused on the sustained release of loaded EPO over a long period of time in peripheral nervous system injury models to guarantee a stable blood concentration on the concentration-time curve [35,36]. However, EPO shows a limited therapeutic time window (within 6-8 h) in in vitro models and in vivo small animal models of CNS injury [5][6][7]37]. Therefore, in clinical situations, the delivery and release of EPO should be as fast as possible for effective neuroprotective actions instead of sustained long-term release.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to delivery studies with other therapeutics, most EPO delivery trials have focused on the sustained release of loaded EPO over a long period of time in peripheral nervous system injury models to guarantee a stable blood concentration on the concentration-time curve [35,36]. However, EPO shows a limited therapeutic time window (within 6-8 h) in in vitro models and in vivo small animal models of CNS injury [5][6][7]37]. Therefore, in clinical situations, the delivery and release of EPO should be as fast as possible for effective neuroprotective actions instead of sustained long-term release.…”
Section: Discussionmentioning
confidence: 99%
“…To trigger the neuroprotective actions of EPO, the extrahematopoietic EPO receptor signaling pathway should be activated, which subsequently activates downstream mediators including the JAK2/signal transducer and activator of transcription 5 (STAT5) and phosphoinositide-3-kinase (PI3K)/protein kinase B (AKT) [5,37,47,48]. In the current study, compared with EPO, ENBs with preconditioning sonication showed delayed and reduced induction of JAK2 expression against TG-induced cytotoxicity before 24 h. This finding might have been caused by the greater time lag for alginate polymer breakdown and subsequent greater EPO release from ENBs than expected [19].…”
Section: Discussionmentioning
confidence: 99%
“…Attaching Fe 3 O 4 to the NPs provides autonomous propulsion and superparamagnetic properties to the nanobot system ( Andhari et al, 2020 ), suggesting a potential of the targeted delivery to deeply located lesions within the CNS. However, using an external magnetic field is difficult in tissues greater than 2 cm deep within the body, as the aforementioned advantages of magnetic field-mediated directional navigation sharply decrease with increasing distance between the magnets and the carriers ( Hwang, 2020 ). Although internal methods such as the implantation of magnets within the body have been devised as an alternative (e.g., intrathecal implant; Lueshen et al, 2015 ), implants can trigger side effects such as infection and intolerance to them ( Ganz, 2017 ).…”
Section: Magnetic Field-mediated Deliverymentioning
confidence: 99%
“…200,201 On top of that, it has been suggested that chemical stimuli, such as growth factors, should be added to the materials to better regenerate CNS tissues. 202,203 To achieve the above goals, chemically cross-linkable hydrogels using initiators with lower cytotoxicity are more suitable for CNS regeneration because of their controllable mechanical properties, ionic conductivity, and biocompatibility. For instance, Pawelec et al facilitated the synthesis of PCL hydrogels with a suitable porous structure for spinal-cord reconstruction by applying NaCl as the chemical cross-linking initiator.…”
Section: Tissue Regeneration By Hydrogels With Appropriate Cross-link...mentioning
confidence: 99%